COVID‐19 fatality prediction in people with diabetes and prediabetes using a simple score upon hospital admission. Issue 2 (4th December 2020) - Sourij, Harald; Aziz, Faisal; Bräuer, Alexander; Ciardi, Christian; Clodi, Martin; Fasching, Peter; Karolyi, Mario; Kautzky‐Willer, Alexandra; Klammer, Carmen; Malle, Oliver; Oulhaj, Abderrahim; Pawelka, Erich; et al.
Abstract: Aim: To assess predictors of in‐hospital mortality in people with prediabetes and diabetes hospitalized for COVID‐19 infection and to develop a risk score for identifying those at the greatest risk of a fatal outcome. Materials and Methods: A combined prospective and retrospective, multicentre, cohort study was conducted at 10 sites in Austria in 247 people with diabetes or newly diagnosed prediabetes who were hospitalized with COVID‐19. The primary outcome was in‐hospital mortality and the predictor variables upon admission included clinical data, co‐morbidities of diabetes or laboratory data. Logistic regression analyses were performed to identify significant predictors and to develop a risk score for in‐hospital mortality. Results: The mean age of people hospitalized (n = 238) for COVID‐19 was 71.1 ± 12.9 years, 63.6% were males, 75.6% had type 2 diabetes, 4.6% had type 1 diabetes and 19.8% had prediabetes. The mean duration of hospital stay was 18 ± 16 days, 23.9% required ventilation therapy and 24.4% died in the hospital. The mortality rate in people with diabetes was numerically higher (26.7%) compared with those with prediabetes (14.9%) but without statistical significance ( P = .128). A score including age, arterial occlusive disease, C‐reactive protein, estimated glomerular filtration rate and aspartate aminotransferase levels at admission predicted in‐hospital mortality with a C‐statistic of 0.889 (95% CI: 0.837‐0.941) and calibration of 1.000 ( P = .909). Conclusions: The in‐hospital mortality for COVID‐19 was high in people with diabetes but not significantly different to the risk in people with prediabetes. A risk score using five routinely available patient variables showed excellent predictive performance for assessing in‐hospital mortality.